Registros de ocorrência e novos hospedeiros de Gargaphia lunulata (Mayr) (Hemiptera: Tingidae) nos estados do Acre e Paraná - Santos, Rodrigo Souza; Hata, Fernando Teruhiko; Coelho, Luci Boa Nova; Ventura, Mauricio Ursi (EntomoBrasilis, 2017)
Resumo. Foi observada a ocorrência de colônias do percevejo-de-renda Gargaphia lunulata (Mayr) (Hemiptera: Tingidae) em folhas de quatro plantas hospedeiras: arruda (Ruta graveolens L.) e feijão-de-porco (Canavalia ensiformis (L.) DC), em jardim residencial urbano, no Município de Rio Branco, AC e crotalária, Crotalaria spectabilis Roth, feijão-de-porco e quiabeiro (Abelmoschus esculentus L. Moench), em casa de vegetação, no Município de Londrina, PR. As colônias encontravam-se exclusivamente na face abaxial das folhas, causando clorose, murchamento e senescência precoce das mesmas. Pelo fato de G. lunulata ser considerada uma importante praga do maracujazeiro no Brasil, o plantio das espécies vegetais citadas, em consórcio ou próximas a cultivos de maracujá, não seria recomendado, pois poderiam servir como fonte de inóculo à cultura do maracujazeiro. Faz-se, portanto, o primeiro registro da ocorrência de G. lunulata associada à arruda e feijão-de-porco no estado do Acre e C. spectabilis, feijão-de-porco e quiabeiro, no estado do Paraná. Ademais, o presente trabalho faz o primeiro relato de ocorrência desse tingídeo para os estados do Acre e Paraná e relata dois novos hospedeiros para esse inseto, R. graveolens e C. spectabillis no Brasil. Occurrence records and new hosts of Gargaphia lunulata (Mayr) (Hemiptera: Tingidae) in the states of Acre and Paraná, Brazil Abstract. The occurrence of Gargaphia lunulata (Mayr) (Hemiptera: Tingidae) was observed in leaves of four host plants: rue (Ruta graveolens L.) and jack bean (Canavalia ensiformis (L.) DC ) in an urban residential garden, in the municipality of Rio Branco, Acre State, Brazil and Crotalaria spectabilis (L.), jack bean and okra (Abelmoschus esculentus L. Moench) in a greenhouse, in the municipality of Londrina, Paraná State, Brazil. The colonies were found exclusively on the abaxial face of the leaves, causing chlorosis, wilting and early senescence of the same. Because G. lunulata is considered to be an important passion fruit pest in Brazil, the planting of the mentioned plant species, in intercropping or near to passion fruit crops, would not be recommended, since they could serve as plant species inoculum to passion fruit cultivation. Therefore, the occurrence of G. lunulata associated to R. graveolens and jack bean in Acre State; and C. spectabilis, jack bean, and okra, in Paraná State is record for the first time. In addition, the present work reports the first occurrence of this tingid to the States of Acre and Paraná and reports two new hosts for this insect, R. graveolens and C. spectabillis in Brazil.